Agronomic and Environmental Impacts of Giant Reed (Arundo donax L.): Results from a Long-Term Field Experiment in Hilly Areas Subject to Soil Erosion - Fagnano, M; Impagliazzo, A; Mori, M; Fiorentino, N (Bioenergy research, 2015)
Of the various biomass crops, one of the most promising for bioenergy or biochemical production is giant reed (Arundo donax L.): It is tolerant to a wide range of environmental stresses and can therefore be cultivated on marginal lands which cannot be used for traditional food crops. An open field experiment was carried out in a soil subjected to accelerated erosion so as to evaluate the agronomic and environmental impact of giant reed during the first 9 years of cultivation. In a low-input cropping system, the crop gave an interesting biomass yield and gross income when grown on marginal hilly lands in southern Italy affected by climatic constraints and accelerated erosion. Its cultivation had favourable effects on environmental quality, thanks to the improvement in soil fertility (soil organic matter and N increase), mitigation of climate change (C storage in the soil) and reduction in soil loss by erosion (reducing soil erodibility and increasing vegetation cover). Winter harvest was found to be more advisable because it reduced biomass moisture and N content, thus improving biomass quality (fewer problems in storage and industrial use) and cropping system sustainability (higher N return to the soil and hence less need for N fertilization).